Assessment of School Safety Planning on Staff Job Performance in Ilorin West Local Government Area, Kwara State - Shittu, Afeez Adeshina; Sheu, Muritala Adaramaja; Aruekure, Nuvie Nunu Brown-Ovie; Alao, Monsurat Iyabo; Zakariyawu, Adam (PAEDAGOGIA, 2000)
School safety has become a critical concern in educational systems due to rising incidents of violence, insecurity, and infrastructural vulnerabilities that threaten effective teaching and learning. In Nigeria, persistent security challenges have heightened the need for structured safety planning within schools. Despite growing attention to school security, limited empirical evidence exists on how specific dimensions of safety planning influence staff job performance at the local level. This study assessed the relationship between school safety planning and staff job performance in public senior secondary schools in Ilorin West Local Government Area, Kwara State. A descriptive survey research design of the ex post facto type was adopted. The population comprised 1,521 teaching and non-teaching staff, from which 150 respondents were selected using a multi-stage sampling procedure. Data were collected using a validated questionnaire with a reliability coefficient of 0.81. Descriptive statistics (mean and standard deviation) were used to answer research questions, while Pearson Product-Moment Correlation was employed to test four hypotheses at the 0.05 level of significance. Findings revealed that technological security planning ranked highest among safety dimensions, while physical security planning ranked lowest. The overall level of staff job performance was high. All four dimensions—human, policy, physical, and technological security planning—showed statistically significant positive relationships with staff job performance. The study concludes that structured, multidimensional safety planning enhances staff effectiveness and institutional productivity. It contributes localised empirical evidence linking school safety planning directly to staff job performance in Kwara State